Virtual Consultations: Young People and Their Parents’ Experience - Proulx-Cabana, Stephanie (Adolesc Health Med Ther, 2021)
PURPOSE: Evaluate the experience of virtual consultations for young people and their families and assess whether young people are being offered a confidential space as part of these virtual encounters. PATIENTS AND METHODS: An anonymous online survey was sent to young people age 10–18 y.o. who had experienced at least one virtual consultation with an adolescent medicine tertiary service in the United Kingdom between March 13th and June 13th 2020 mostly associated with, but not exclusively, management of chronic fatigue syndrome or medically unexplained symptoms. Responses from the survey were analysed by two authors who independently coded the common themes reported by the participants. RESULTS: Fifty young people and their families participated in the survey. Eighty-eight percent reported feeling prepared for virtual appointments, 90% found them helpful, 88% felt that they were private and 86% reported they would find further virtual appointments helpful. Positive impacts reported were no need to travel (38%) and the continuity of care (36%). Many of our participants reported no negative impact (39%) and felt that nothing needed to be improved (56%). The most frequent improvement reported was the provision of a quality video call (34%). Only 36% of young people had the opportunity to speak in confidence to the health care provider without their parents’ presence. CONCLUSION: Virtual appointments are perceived as safe and helpful by the young people and their families. Professionals should offer a confidential remote space for young people to speak without their parents.